The World Health Organization reforms in the time of COVID-19 - Germán Velásquez (South Centre, 2020)
During its 70-year history, the World Health Organization (WHO) has undergone various reforms led by several Directors-General, including Halfdan Mahler at the Almaty Conference on primary health care in 1978, Gro Harlem Brundtland with her “reach out to the private sector” in 1998, and Margaret Chan with her unfinished debate on the role of “non-state actors” in 2012. The organization's fragility is once again being highlighted, as the COVID-19 pandemic has revealed that WHO does not have the legal instruments and mechanisms necessary to enforce its standards and guidelines, and that its funding is not sustainable and adequate to respond to the challenge. This paper seeks to identify the main problems faced by WHO and the necessary measures that a reform of the organization would have to take.
Keywords: 300; Article 19 WHO Constitution; Coronavirus; COVID-19; France; Germany; Global Health; Health; International Health Regulations (IHR); Non-Paper on Strengthening WHO; Pandemic; Public Health; WHO; WHO Executive Board (EB); WHO Reform; World Health Assembly (WHA); World Health Organization